Macroeconomic analysis of population ageing in middle-income countries / Yip Tien Ming - Yip , Tien Ming (2023)
Many middle-income countries experienced rapid population ageing at the turn of the 21st century. However, limited research focuses on the causes and consequences of population ageing in this group of countries. Moreover, the issue of population ageing is amplified due to the growing concern that many middle-income countries are economically unprepared to embrace the increasing ageing population. Using a panel of cross-country dataset that covers 64 middle-income countries from 1996 to 2019, this thesis conducts three empirical analyses on the demographic determinants of population ageing, the macroeconomic implications of population ageing, and the moderating effect of labour force participation of older persons in the economic growth-population ageing relation. First, this thesis identifies the primary driver of population ageing by comparing the impact of fertility and mortality changes on population ageing. The empirical results provide robust evidence that the fertility rate dominates in accelerating population ageing. Additional comparative analysis between demographic and macroeconomic variables further ascertains the role of fertility rate in influencing population ageing. Further analysis indicates that fertility-driven population ageing is associated with lower economic growth. Second, this thesis formally examines the macroeconomic implications of population ageing by assessing the association between economic growth and population ageing. The empirical results provide robust evidence that population ageing is inversely and significantly associated with economic growth. More importantly, the economic impact of population ageing is substantial and larger than the conventional determinants of economic growth. Further analysis shows that population ageing adversely affects economic growth by reducing aggregate savings, labour force growth, and total factor productivity growth. Third, in light of the growth-deteriorating effect of population ageing, this thesis takes a further step to explore the moderating effect of labour force participation of older persons in the economic growth-population ageing nexus. The empirical results provide robust evidence that a higher older persons’ labour force participation rate mitigates the adverse impact of population ageing on economic growth. Further analysis shows that older persons’ labour force participation mitigates the growth-deteriorating effect of population ageing by compensating for the loss of aggregate savings, labour force growth, and total factor productivity growth induced by population ageing. Moreover, disaggregated analysis using gender-specific older persons’ labour force participation rate provides additional insights that older female and male workers are equally important in offsetting the adverse impact of population ageing on economic growth. Additional analysis found that a higher older persons’ labour force participation rate leads to a better labour market outcome for younger workers. The results suggest that promoting older persons’ labour force participation is economically feasible to offset the growth-deteriorating effect of population ageing. Regarding policy implications, this thesis urges policymakers in middle-income countries to recognise the scope of the new demographic trend and implement policy measures to counter the adverse effect of population ageing on economic growth. One effective way to accommodate the macroeconomic implications of population ageing is to promote the labour force participation of older persons.